Perencanaan Sistem Pengelolaan Sampah Berbasis Masyarakat Di Desa Banuroja, Kecamatan Randangan, Kabupaten Pohuwato - Fatah Galang Fauzi; Nur Inda R. Umadji; Siti Amalia Gobel (Universitas Negeri Gorontalo, 2025)
Waste management in Banuroja Village, Pohuwato Regency, currently faces significant obstacles in the form of low public awareness and a lack of integrated management infrastructure. This study aims to analyze the existing condition of waste management and design an effective and sustainable system. The research method used field observations and measurement of waste generation and volume for 8 consecutive days based on SNI 19-3964-1994. The results showed that the average waste generation at the study site reached 53.2 kg/day or equivalent to 0.266 m³/day, with organic waste as the dominant characteristic. Existing conditions indicate that the community still practices open burning and dumping waste into water bodies. The system development plan includes providing individual waste containers, a scheduled collection system, organic waste processing through composting, and applying 3R principles for inorganic waste. The implementation of this system is expected to reduce the impact of environmental pollution and improve the health status of the village community.